Automate IGP and EGP Routing Protocol Configuration using a Network Automation Library - Yuansa Alfaresa; Bongga Arifwidodo; Fauza Khair (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2023)
Data communication is sending data from client to client through a computer network. The increasing use of data communication makes computer networks more complex. Complex computer networks make it difficult for network administrators to configure them, especially routing protocol configuration. Network administrators are in charge of configuring routing protocols and managing networks. In addition, the more devices on the network, the greater the chance of human error from the administrator. Therefore, network automation is one solution that helps network administrators overcome this. This study focuses on analyzing the performance of network automation using the Paramiko and Telnetlib libraries. The routing protocol used by OSPF for IGP and BGP for EGP. The scenario in this study involves configuring IP addresses and configuring OSPF and BGP routing. Based on the test results, the Telnetlib library is better than the Paramiko library in terms of script delivery time, convergence time, and delay by 19.237% when applied to the IGP and EGP routing protocols.